Towards Good Governance of Premarital Course for Muslims in Malaysia - Saidon, Rafeah; Ishak, Amal Hayati; Alias, Baterah; Ismail, Fadhilah Adibah; Aris, Suliah Mohd (International Review of Management and Marketing, 2016)
A premarital course is a two-day course which is made compulsory to Muslims in Malaysia. The current study attempts to propose good governance of premarital course for Muslims in Malaysia by investigating the loopholes of the existing system. Qualitative method is used in which administrative procedures and formalities are studied and analysed. This research also employed a semi structured interviews conducted on several respondents from the related institutions. This study is perhaps one of the first to highlight the weaknesses of premarital course for Muslims in Malaysia and propose good governance particularly from both legal and administrative perspectives. Findings of this research show some significant weaknesses in the present governance of premarital course and a new model of governance is proposed for the betterment of Muslim families in Malaysia. The findings provide on how the legal and administrative mechanism relating to premarital course can be improved and subsequently aid the relevant authorities or institutions involved in policy making pertaining to family matters and its implementation. Keywords: good governance, premarital course, Muslims, Malaysia JEL Classifications: C610, C623, I23